AVALIAÇÃO DO POTENCIAL DE BIOMASSA EM FLORESTAS DE EUCALIPTO UTILIZANDO SENSORES REMOTOS - Barros, Bruna Soares Xavier de; Barros, Zacarias Xavier de (ENERGIA NA AGRICULTURA, 2024)
ASSESSMENT OF BIOMASS POTENTIAL IN EUCALYPTUS FORESTS USING REMOTE SENSING BRUNA SOARES XAVIER DE BARROS1, ZACARIAS XAVIER DE BARROS2 1 Department of Rural Engineering and Socioeconomics, School of Agricultural Sciences, São Paulo State University UNESP, Zip Code 18610-034, Botucatu, SP, Brazil, brunasxb@gmail.com. 2 Department of Rural Engineering and Socioeconomics, School of Agricultural Sciences, São Paulo State University UNESP, Zip Code 18610-034, Botucatu, SP, Brazil, zacarias.barros@unesp.br. ABSTRACT: The search for renewable energy combined with the socio-economic importance of Eucalyptus cultivation has opened new avenues for Eucalyptus application beyond the traditional uses. In this study, the Geographical Information System (GIS) was applied to evaluate the distribution of Eucalyptus stands in Botucatu SP, Brazil. The GIS also assisted in the calculation of the potential biomass with satellite images. Satellite images were captured by the Land Operational Imager (OLI), installed aboard the Landsat-8 satellite and made available by the United States Geological Survey (USGS) / Earth Resources Observation & Science Center (EROS). Results from this study showed that the area covered by the Eucalyptus forest in Botucatu corresponds to a maximum of 197.04 tons per hectare of biomass, representing more than 10% of its area. Therefore, it is possible to use remote sensing images to expand the capacity to generate information on forest registries. These results may be very useful to companies that use the raw materials from these planted forests. Keywords: satellite images, geoprocessing, GIS. AVALIAÇÃO DO POTENCIAL DE BIOMASSA EM FLORESTAS DE EUCALIPTO UTILIZANDO SENSORES REMOTOS RESUMO: A busca por energia renovável, combinada com a importância socioeconômica do cultivo de eucalipto, abriu novas avenidas para a aplicação do eucalipto além dos usos tradicionais. Neste estudo, o Sistema de Informação Geográfica (SIG) foi aplicado para avaliar a distribuição dos talhões de eucalipto em Botucatu, SP, Brasil. O SIG também ajudou no cálculo do potencial de biomassa com imagens de satélite. As imagens de satélite foram capturadas pelo Land Operational Imager (OLI), instalado a bordo do satélite Landsat-8, e disponibilizadas pelo Serviço Geológico dos Estados Unidos (USGS) / Centro de Observação e Ciência de Recursos da Terra (EROS). Os resultados deste estudo mostraram que a área coberta pela floresta de eucalipto em Botucatu corresponde a um máximo de 197,04 toneladas por hectare de biomassa, representando mais de 10% de sua área. Portanto, é possível usar imagens de sensoriamento remoto para expandir a capacidade de gerar informações sobre os registros florestais. Esses resultados podem ser muito úteis para empresas que utilizam as matérias-primas dessas florestas plantadas. Palavras-chave: imagens de satélite, geoprocessamento, SIG.